WORKING CAPITAL MANAGEMENT AND THE INFLUENCE OF BEHAVIORAL FINANCE: THE CASE OF a DAIRY COMPANY - Cerchi, Ana Luisa Rezende [UNESP]; Santos, David Ferreira Lopes (Fundacao Pedro Leopoldo, 2023)
Purpose of the study: to understand working capital management in a large dairy company in the state of Minas Gerais, based on the behavioral approach to finance. Methodology: the research strategy based on a single case was chosen, combining quantitative and qualitative analysis tools Originality: extending the analysis of behavioral biases in decisions on investments in financial assets to the management of working capital. Main results: it was found that the most liquid accounts are those influenced by more behavioral biases. The biases present in decision-making are also consistent with the conservative profile indicated by the dynamic working capital management model. Theoretical contributions: the theoretical trade-off liquidity and profitability does not occur since a higher level of liquidity can be caused precisely by the greater profitability and cash generation capacity of the company compared to the sector. Managerial contributions: the management of working capital must assume a more strategic condition in companies and attentive to the behavioral biases of managers. As a result of the direct impacts of marketing and production policies on investment in working capital, the analysis of indicators must be aligned with the company's profile.
Keywords: Dynamic Working Capital Model; Profitability; Liquidity; Dairy Sector